Computer animation algorithms and techniques - Parent, Rick. (San Francisco : Morgan Kaufmann Publishers, 2002)
Whether you're a programmer developing new animation functionality or an animator trying to get the most out of your current animation software, Computer Animation: Algorithms and Techniques will help work more efficiently and achieve better results. For programmers, this book provides a solid theoretical orientation and extensive practical instruction-information you can put to work in any development or customization project. For animators, it provides crystal-clear guidance on determining which of your concepts can be realized using commercially available products, which demand custom programming, and what development strategies are likely to bring you the greatest success. * Expert instruction from a pace-setting computer graphics researcher. * Provides in-depth coverage of established and emerging animation algorithms. * For readers who lack a strong scientific background, introduces the necessary concepts from mathematics and physics. * Illustrates advanced programming techniques with highly detailed working examples. * Via the companion Web site, provides lecture notes from the author's course for professors, example animations based on the programs covered in the book, Java applets, and links to relevant Web sites. * Special contributions from Dave S. Ebert on Natural Phenomena in Chapter 5 * Special contributions from Scott King, Meg Geroch, Doug Roble, and Matt Lewis on Articulated Figures in Chapter 6.
Foreword -- Preface -- Chapter 1 -- Introduction -- Chapter 2 -- Technical Background -- Chapter 3 -- Interpolation and Basic Techniques -- Chapter 4 -- Advanced Algorithms -- Chapter 5 -- Natural Phenomena -- Chapter 6 -- Modeling and Animating Articulated Figures -- Appendix A -- Rendering Issues -- Appendix B -- Background Information and Techniques -- Index -- About the Author.
Includes bibliographical references and index.
Keywords: Computer animation; Electronic books